The Influence of Awareness, Knowledge and Sanctions On Compliance Retribution Users Flats With Technology Information As Variables Moderation - Ramadhanti, Salsabilla (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This paper aims to examine the power of information technology in moderating the relationship between awareness, knowledge and sanctions on compliance with flat user fees. This research is important because looking at previous studies produces different conclusions. Samples were taken using the simple random sampling method. The sample size was 122 flat residents who had lived there for more than 2 years. A quantitative approach is used to collect and analyze numerical data that can be measured and processed statistically where the survey method is given to respondents using purposive sampling. This research uses data analysis with Structural Equation Modeling (SEM) techniques. The results of the study concluded that awareness, knowledge and sanctions had a positive effect on compliance with flat user fees. However, when including technological information as a moderating variable, it is shown that awareness, knowledge and sanctions do not strengthen the relationship to compliance with flat user fees. This article has implications for the UPTD for Flats to coordinate with Bapenda to be able to integrate the existing QRIS with e-Retribution, and further consider factors that can increase Bogor City regional levies, especially Bogor City regional income related to flat rental levies. Keywords: Awareness, Knowledge, Sanctions, Rusunawa User Retribution Compliance, and Information Technology